Biodiversity Loss and Its Impact on Dietary Land Diversity and Nutritional Status: A Comprehensive Review - Neelesh Kumar Maurya; Bhawini (International Journal of Land, 2025)
Habitat destruction, climate change, overexploitation, and agricultural intensification contribute to the current predicament in global food systems: Loss of biodiversity means less plant and animal species to be utilized. This study examines and synthesizes the available literature in PubMed and Scopus on how losses in biodiversity adversely affect people’s diets and nutritional status, especially in the case of malnutrition and missing key micronutrients of certain demographic cohorts. Principal factors are loss of agro biodiversity and wild foods, especially fish and other foraged plants, and shifts in diet towards nutritionally poor mono staple foods. Land use change and environmental degradation through the agricultural expansion of the built environment over 70% of terrestrial habitats, deforestation, and loss of soil biodiversity and ecosystem services, disrupt other fundamental underlying factors of food quality. Multiple studies demonstrate that greater biodiversity within foods, as measured with greater Dietary Species Richness (DSR), correlates with better diet and improved health, especially with lower all-cause mortality. In LMICs, for example, declining afro biodiversity correlates to increased micronutrient deficiency and increased anemia and stunting. Of the 9 crops that dominate global production of 66% of total food produced, bio-diversity loss poses problematic risks.Investigating losses of wild-caught species in Amazonian fisheries suggests compensatory dynamics may heighten supplies of certain nutrients, such as omega-3 fatty acids, in the short term, but cause greater long term supply instability in iron and zinc. Environmental scope analysis suggests that land degradation shrinks soil microbial diversity by 50-75%. It consequently reduces the iron and zinc contents of staple cereal crops’ micronutrients by 20-40%. Review articles highlighting food biodiversity inform that over 2 billion people whose diets are centered on wild foods are supplied with greater nutrients, but current patterns evidently increase malnutrition risk. Strategies to mitigate the negative impacts include the promotion of neglected but underutilized species, sustainable food production and greater policy integration around health, agriculture and conservation
Keywords: Climate change; Land biodiversity; agricultural; overexploitation; sustainable food